Construction and evaluation of a short version of the sexual scripts overlap scale - Landripet, Ivan; Štulhofer, Aleksandar (2008)
The Sexual Scripts Overlap Scale (SSOS) is a novel instrument developed by the authors to measure potential effects of SEM on sexual socialization. The full version of the scale has already been implemented in a couple of recently published studies. It proved a useful tool in testing theoretical models of a mediated impact of SEM use on sexual satisfaction. The objective of this study was to develop a valid and reliable abbreviated version of the original measure, which would enable wider application of the instrument. The SSOS was developed by asking separate groups of college students of both sexes to make a list of things/activities/sensations important for pornographic depiction of sex, and of those that are personally important for great sex (N=76). Judged for relevance and occurrence, 42 items were selected and combined into the final inventory. In the 2006 online questionnaire (N=2, 092, 18-25 years of age), participants were first asked to assess the importance of the listed items for “great sex” and, later on, for "pornographic presentation of sex.” The SSOS scores were computed on each of the 42 paired items (the great sex vs. the porn inventory) by subtracting the second result from the first. The scale is additive: the higher the total score, the lower the overlap between the scripts (the SSOS scores ranged from 0 to 143 and were distributed in a Gauss-like fashion ; M= 71.7, SD = 21.6). To make the scale more economic, an attempt was made to shorten the SSOS. Items from both inventories were ranged by means (data from the 2006 study and its sequel from 2007 /N=600/ were used) to determine the most characteristic aspects of both “great sex” and “pornographic sex” scripts. Top ten items from the great sex inventory corresponded in both samples, as did nine items from the porn inventory. The resulting 19-item scale was expected to provide a more rigorous measure of the scripts overlap (the SSOS-S scores ranged 0-68 and were normally distributed ; M=32.7, SD=10.7). Correlations between the SSOS and its short version (SSOS-S) were high in both samples (around .9) ; Cronbach's α for the SSOS-S was 0.83. Principal component analysis indicated the presence of four significant dimensions with a strong tendency towards a two-domain solution: 10 items loaded highly on the “intimacy” factor (α = .86) and the remaining nine on the “sexual performance” factor (α = .76). Construct validity was assessed by testing associations between the SSOS-S and the frequency of past and present SEM use, real-life desirability of pornographic sex, attitudes towards SEM and the personal importance of SEM scale. All correlations were significant and, in most cases, of moderate strength. As expected, women demonstrated lesser overlap then men (their average SSOS-S score was significantly higher). Current users of paraphilic SEM reported higher overlap than those who prefer mainstream SEM. Pending further tests and analyses, our preliminary assessment suggested sound metric properties of the SSOS-S. The use of this relatively short composite indicator of the sexual script overlap could improve our understanding of the impact of SEM use on young people’s sexual socialization and sexual behavior.
Projekt MZOS
ENG